Implementasi Metode Double Exponential Smoothing untuk Sistem Peramalan Penjualan Alat Musik - Ilham, Mohammad Akbar; Achmadi, Sentot; Sari, Karina Aulia (Jurnal Teknologi Terpadu, 2024)
EMC-Emmanuel Music Centre is a company that sells musical instruments and sound systems with the aim of advancing music and professional audio in Indonesia. This research aims to forecast the monthly sales of musical instruments to better manage sales data and develop more efficient sales strategies. The method used is Double Exponential Smoothing, a forecasting technique in data mining. The research subjects were the company's musical instrument sales data, with a population covering all sales transactions from January 2022 to January 2024. The sample was selected using purposive sampling, focusing on transaction data of top-selling products. Data was collected through interviews, direct observations of the sales process, and review of marketing strategy documents. The results show that the Double Exponential Smoothing method produces forecasts with an average MAE of 8.12%, categorized as very good. This study recommends using forecast results for inventory management and adjusting seasonal marketing strategies to improve efficiency. The results indicate that an alpha  of 0.1 provides better accuracy with an MAE of 17.08, compared to an alpha  of 0.2 with an MAE of 19.08. Therefore, an alpha  of 0.1 is recommended for improving the forecasting accuracy.